Application of a ZnO@Fe3O4 composite catalytic material in plant waste treatment

CN122894976APending Publication Date: 2026-10-13CHINA UNIV OF GEOSCIENCES (BEIJING)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611311030.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0003]随着农业生产规模不断扩大以及城市园林废弃物、食品加工副产物等植物性有机固废持续增加,传统填埋、焚烧或简单堆肥等处理方式已难以满足高效、环保和资源化利用的发展需求

Benefits of technology

本发明通过在含ZnO@Fe3O4复合催化材料的体系中施加交流电场,可强化体系内的物质传递过程,促进有机物分解和转化,从而提高植物废弃物的处理效率,缩短处理周期,并提升资源转化率。同时,该技术能够与堆肥、厌氧发酵、生物精炼等多种处理工艺相结合,形成多技术协同的资源化利用模式,进一步提高废弃物的综合利用价值。该技术有望在农业废弃物处理、有机固废资源化利用以及生物质能源开发等领域得到更加广泛的应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122894976A_ABST
    Figure CN122894976A_ABST
Patent Text Reader

Abstract

The application discloses application of a ZnO@Fe3O4 composite catalytic material in plant waste treatment and belongs to the technical field of agricultural waste treatment. A plant waste treatment liquid is added into a double-electrode reaction device, a working electrode of the double-electrode reaction device is carbon cloth coated with ZnO@Fe3O4 composite catalytic material, and a counter electrode is a carbon rod; and plant waste is degraded through alternating current treatment at room temperature. By applying an alternating current field in a system containing the ZnO@Fe3O4 composite catalytic material, the application can strengthen the material transfer process in the system, promote the decomposition and conversion of organic matter, thereby improving the treatment efficiency of the plant waste, shortening the treatment period, and improving the resource conversion rate. Meanwhile, the technology can be combined with multiple treatment processes such as composting, anaerobic fermentation, biological refining and the like to form a resource utilization mode of multiple technology cooperation, and further improve the comprehensive utilization value of the waste.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of agricultural waste treatment technology, and in particular relates to the application of a ZnO@Fe3O4 composite catalytic material in the treatment of plant waste. Background Technology

[0002] With the continuous expansion of agricultural production and the rapid development of the food processing industry, a large amount of plant waste (such as crop straw, fruit and vegetable residues, and garden trimmings) is constantly generated during production and consumption. This type of waste is typically rich in lignocellulose components such as cellulose, hemicellulose, and lignin, making it an important renewable biomass resource. Improper handling can not only lead to resource waste but also trigger a series of ecological and environmental problems, such as greenhouse gas emissions, soil degradation, and eutrophication of water bodies. Studies show that the amount of organic waste globally continues to grow, and traditional landfill or incineration methods are not only inefficient but may also generate secondary pollution, posing potential risks to the ecological environment and human health. Plant waste is increasingly being recognized as a biomass resource with enormous development potential. Agricultural biomass waste is rich in nutrients such as carbon and nitrogen, and through appropriate technological means, it can be converted into biofuels, biomaterials, and high-value-added chemicals, achieving resource utilization that "turns waste into treasure." Related research indicates that agricultural waste can not only be used to produce bioenergy but also to prepare organic fertilizers, functional materials, and bio-based chemicals, playing a significant role in alleviating the energy crisis and reducing greenhouse gas emissions.

[0003] With the continuous expansion of agricultural production and the increasing amount of plant-based organic solid waste such as urban garden waste and food processing by-products, traditional treatment methods such as landfill, incineration or simple composting are no longer sufficient to meet the development needs of efficient, environmentally friendly and resource-based utilization. Summary of the Invention

[0004] To address the aforementioned problems, this invention provides an application of a ZnO@Fe3O4 composite catalytic material in plant waste treatment. By combining zinc oxide and iron tetroxide to obtain the ZnO@Fe3O4 composite catalytic material, it is used as an alternating current catalyst for the efficient conversion of plant waste, showing promising application prospects. Electric field technology, due to its mild reaction conditions, controllable process, and environmental friendliness, is gradually becoming an important research direction in the field of biomass treatment.

[0005] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: The application of a ZnO@Fe3O4 composite catalytic material in the treatment of plant waste includes the following steps: adding the plant waste treatment liquid into a two-electrode reaction device, wherein the working electrode of the two-electrode reaction device is a carbon cloth coated with ZnO@Fe3O4 composite catalytic material, the counter electrode is a carbon rod, and the plant waste is degraded by alternating current treatment at room temperature.

[0006] Furthermore, the frequency of the AC power processing is 1μHz-1000Hz, and the AC power processing time is 60-180min.

[0007] Furthermore, the electrical signal waveform of the AC power processing is selected from sine wave, triangle wave, square wave, noise wave, pulse wave or singer function waveform.

[0008] Furthermore, the electrical signal waveform of the AC power processing is selected from the Singer function waveform.

[0009] Furthermore, the frequency of the AC power processing is 10 Hz, and the AC power processing time is 180 min.

[0010] Alternating current (AC) treatment technology offers numerous advantages in the resource utilization of plant waste. By applying an AC electric field to the plant waste system, effects such as electromigration, electroosmosis, and polarization can be generated, thereby promoting mass transfer within the system and disrupting some plant cell structures. This makes complex organic components such as cellulose, hemicellulose, and lignin more readily degraded, improving the conversion efficiency of organic matter. Simultaneously, the AC electric field can stimulate microbial activity to a certain extent, enhancing microbial metabolism and the function of related enzymes, accelerating bioconversion processes such as composting or fermentation, thus shortening the treatment cycle. Furthermore, AC treatment can achieve more uniform internal heating through the Joule effect, improving energy utilization efficiency and avoiding the uneven heat transfer problems present in traditional external heating methods. At the same time, AC treatment does not require the addition of large amounts of chemical agents, reducing the risk of secondary pollution.

[0011] Furthermore, the preparation method of the ZnO@Fe3O4 composite catalytic material includes the following steps: adding zinc nitrate hexahydrate and hexamethylenetetramine to water, mixing well to obtain a precursor solution, adding ferric nitrate nonahydrate to the precursor solution, continuing to mix well, carrying out a hydrothermal reaction, cooling to room temperature, centrifuging, washing, and drying to prepare the ZnO@Fe3O4 composite catalytic material.

[0012] Furthermore, the molar ratio of zinc nitrate hexahydrate, hexamethylenetetramine, and ferric nitrate nonahydrate is 12:12:1; the hydrothermal reaction temperature is 95°C, and the reaction time is 4 hours.

[0013] The ZnO@Fe3O4 composite catalytic material prepared by this invention has the following advantages: 1. Highly efficient AC electrocatalytic performance: The synergistic effect of ZnO and Fe3O4 significantly improves the catalytic performance of the material; 2. Excellent stability: The ZnO@Fe3O4 composite catalytic material exhibits good stability during long-term electrocatalytic reactions and can maintain high catalytic efficiency; 3. Broad-spectrum degradation ability: This ZnO@Fe3O4 composite catalytic material shows excellent degradation effects on a variety of plant wastes.

[0014] Furthermore, the preparation method of the plant waste treatment liquid includes the following steps: drying and pulverizing the plant waste, adding the obtained plant waste powder to a mixed solvent of N-methylpyrrolidone and water to obtain the plant waste treatment liquid.

[0015] Furthermore, the volume ratio of N-methylpyrrolidone to water is 4:6; the ratio of plant waste powder to mixed solvent is 0.62g:35mL.

[0016] Technical principle of the invention: The invention employs an alternating current electrocatalytic mechanism. During the alternating current electrocatalytic degradation process, an alternating current electric field drives a dual-pathway oxidation mechanism, in which the negative half-cycle generates a large amount of O2. - / H2O2 is used for overall degradation, and the positive half-cycle generates surface-limited ·OH, which can effectively transform plant waste.

[0017] Compared with the prior art, the present invention has the following advantages and technical effects: This invention enhances mass transfer processes within a system containing ZnO@Fe3O4 composite catalyst by applying an alternating electric field, promoting the decomposition and transformation of organic matter. This improves the treatment efficiency of plant waste, shortens the treatment cycle, and increases resource conversion rates. Furthermore, this technology can be combined with various treatment processes such as composting, anaerobic fermentation, and biorefining to form a multi-technology synergistic resource utilization model, further enhancing the comprehensive utilization value of waste. This technology is expected to find wider application in agricultural waste treatment, organic solid waste resource utilization, and biomass energy development. Attached Figure Description

[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0019] Figure 1 The image shows the XRD pattern of the ZnO@Fe3O4 composite catalyst prepared in Example 1. Figure 2 The absorbance was measured after processing for 180 min with sine wave at 1 mHz, square wave at 1 uHz, triangular wave, pulse wave and singer function wave at 10 Hz, and noise without a fixed frequency. Figure 3 The absorbance measured at different frequencies under the Singer function waveform with a processing time of 180 min; Figure 4 The superoxide radical concentration was measured after 180 min of treatment with sine wave at 1 mHz, square wave at 1 uHz, triangular wave, pulse wave and singer function wave at 10 Hz, and noise without a fixed frequency. Figure 5 Hydrogen peroxide concentration was measured after 180 min of processing with sine wave at 1 mHz, square wave at 1 uHz, triangular wave, pulse wave and singer function wave at 10 Hz, and noise without a fixed frequency. Figure 6 The concentration of hydroxyl radicals was measured after 180 min of treatment with sine wave at 1 mHz, square wave at 1 uHz, triangular wave, pulse wave and singer function wave at 10 Hz, and noise without a fixed frequency. Figure 7 A comparison chart showing the degradation trends of pine branches and corn stalk powder. Detailed Implementation

[0020] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0021] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0022] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0023] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0024] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0025] The room temperature in this invention refers to 25±2℃.

[0026] Unless otherwise specified, all materials used in this invention are commercially available products.

[0027] Example 1: A method for preparing a ZnO@Fe3O4 composite catalytic material 0.006 mol of zinc nitrate hexahydrate and 0.006 mol of hexamethylenetetramine were added to 30 mL of deionized water and magnetically stirred continuously for 30 min at room temperature to ensure complete dissolution of the precursors and formation of a homogeneous solution. Then, 0.0005 mol of ferric nitrate nonahydrate was added to the reaction system, and stirring was continued to ensure uniform dispersion. The resulting reaction solution was transferred to a stainless steel reactor with a polytetrafluoroethylene liner, sealed, and placed in a constant temperature oven for a hydrothermal reaction at 95 °C for 4 h. After the reaction, the mixture was allowed to cool naturally to room temperature. The resulting product was separated by centrifugation and repeatedly washed with deionized water to remove residual ions. The precipitate was then dried in a drying oven at 45 °C for 10 h to obtain the ZnO@Fe3O4 composite catalyst. Figure 1 The image shows the XRD pattern of the ZnO@Fe3O4 composite catalyst prepared in Example 1. Figure 1 As can be seen, the diffraction peaks of the composite catalytic material simultaneously contain the characteristic diffraction peaks of ZnO and Fe3O4, and no other obvious impurity peaks appear, indicating the successful composite of the catalyst.

[0028] Application example: AC electrocatalytic test This application example uses pine branches as the research object and systematically carries out alternating current electrocatalytic treatment experiments to evaluate the applicability of the ZnO@Fe3O4 composite catalytic material prepared in Example 1 in biomass systems.

[0029] After thoroughly drying the above-mentioned plant waste, it was prepared into a uniform powder by mechanical pulverization. Then, 0.62 g of plant powder was weighed and added to a 35 mL mixture of NMP (N-methylpyrrolidone) and deionized water (NMP:H2O=4:6 (v / v)) to obtain the plant waste treatment solution.

[0030] 15 mg of the ZnO@Fe3O4 composite catalyst prepared in Example 1 was added to 750 μL of isopropanol and 250 μL of water, and 40 μL of Nafion was added. After mixing, the mixture was coated onto carbon cloth as the working electrode, and a carbon rod was used as the counter electrode to form a two-electrode reaction device.

[0031] Plant waste treatment liquid was added to a two-electrode reactor. An AC signal was applied to the system through an arbitrary waveform signal generator. By adjusting different forms and frequencies of the electrical signal, the catalytic performance of the ZnO@Fe3O4 composite catalytic material was systematically investigated at room temperature.

[0032] The electrical signal waveforms selected in this invention include sine waves, triangle waves, square waves, noise waves, pulse waves, and Singer function waveforms, with frequencies set to 1 μHz, 1 mHz, 1Hz, 10Hz, 100Hz, and 1000Hz, respectively. Under different waveform and frequency combinations, the reaction time for each experiment was controlled to be 180 min. To achieve dynamic monitoring of the catalytic process, 1 mL of solution sample was taken every 60 min during the reaction, diluted 3 times with water, and the absorbance change was measured using UV-Vis spectrophotometry.

[0033] This invention compares the optimal measurement results for each of the following electrical signal waveforms: sine wave, triangle wave, square wave, noise wave, pulse wave, and Singer function waveform. Figure 2 The absorbance was measured after processing electrical signal waveforms at 1 mHz (sine wave), 1 μHz (square wave), 10 Hz (triangular wave), 10 Hz (pulse wave), and 10 Hz (single Hz), with noise at no fixed frequency, for 180 min. Figure 2 As can be seen, using the ZnO@Fe3O4 composite catalyst material prepared in Example 1 as the working electrode, and simultaneously selecting Singer function waveform AC treatment, significant degradation of plant waste can be achieved. Compared with other waveform AC, Singer function waveform AC induces a uniformly distributed and high-intensity electric field throughout the entire electrode region, effectively activating a considerable reaction volume. The noise treatment result is poor because the noise cannot provide sufficient electric field strength and spatial coverage, thus limiting ROS generation to a small and localized situation.

[0034] Figure 3 The absorbance at different frequencies was measured under the Singer function waveform with a processing time of 180 min. Figure 3It can be seen that the absorbance does not change monotonically with frequency. When the frequency is 10Hz, the absorbance reaches its maximum value, indicating that the reaction process is no longer controlled only by the overall energy input intensity, but is closely related to the time structure of the electrical signal. Furthermore, the more complex the system, the wider the characteristic time scale distribution of its internal mass transfer, swelling and bond breaking processes, and the more sensitive it is to the time matching requirements of the applied signal.

[0035] The concentrations of superoxide radicals, hydrogen peroxide, and hydroxyl radicals in a solution sample taken 180 min later were determined. Among them, superoxide radicals (∙O2)... - The concentration was determined using the NBT (nitroblue tetrazolium) reduction method. This method utilizes the reaction of NBT with ·O2. - The maximum absorption peak of NBT after the reaction was located at 259 nm. The degree of NBT reduction was monitored using a UV-2600 spectrophotometer, thereby indirectly determining the ∙O2 content. - The amount of hydrogen peroxide (H2O2) generated. Method for determining hydrogen peroxide (H2O2) concentration: Iodometric method based on potassium iodide (KI) colorimetric reaction. This method involves the reaction of KI with H2O2 to generate elemental iodine, and the concentration of H2O2 is quantitatively determined using the colorimetric reaction. Method for determining hydroxyl radical (∙OH) concentration: Fluorescent probe method, using TA (terephthalic acid) as the detection probe. After the reaction of TA with ∙OH, the product exhibits a characteristic fluorescence emission peak at 425 nm. The fluorescence intensity is measured using a fluorescence spectrophotometer at an excitation wavelength of 315 nm to determine the concentration of ∙OH radicals.

[0036] For the determination of the concentrations of superoxide radicals, hydrogen peroxide, and hydroxyl radicals, this invention compares the optimal measurement results of various electrical signal waveforms, including sine waves, triangular waves, square waves, noise waves, pulse waves, and Singer function waveforms. Figure 4 The superoxide radical concentration was measured after 180 min of treatment with sine waves at 1 mHz, square waves at 1 μHz, triangular waves, pulse waves, and Singer function waves at 10 Hz, without noise at a fixed frequency. Figure 5 Hydrogen peroxide concentrations were measured after 180 min of processing with sine waves at 1 mHz, square waves at 1 μHz, triangular waves, pulse waves, and Singer function waves at 10 Hz, without noise at a fixed frequency. Figure 6 The concentration of hydroxyl radicals was measured after 180 min of processing with sine waves at 1 mHz, square waves at 1 μHz, triangular waves, pulse waves, and singer function waves at 10 Hz, without noise at a fixed frequency. Figure 4-6It can be seen that using the ZnO@Fe3O4 composite catalytic material prepared in Example 1 as the working electrode, and simultaneously applying a Singer function waveform AC current, can generate more superoxide radicals, hydrogen peroxide radicals, and hydroxyl radicals. This is because there is an efficient charge separation pathway at the heterojunction of ZnO@Fe3O4. When a Singer function waveform AC current is applied, its rapid voltage alternation and stable continuous voltage can continuously drive more electrons and holes to participate in the reduction of oxygen and the oxidation of water, respectively, to generate free radicals.

[0037] Based on the previously determined optimal AC treatment parameters (Singer function waveform, frequency 10 Hz) and solvent ratio (NMP∶H2O = 4∶6), this invention further investigates the effect of treatment time on the degradation behavior of different biomass. Pine branches and corn stalk powder (0.62 g) dried to constant weight were weighed and placed in the reaction mixture. The reaction time gradients were set to 24 h, 48 h, and 72 h. After the reaction, the washed precipitate was dried to constant weight in a 50 ℃ constant temperature drying oven, and the residual solid mass at each time point was measured and recorded. The results are as follows: Figure 7 As shown: the mass loss of both biomass in the mixed solvent system increased with increasing treatment time, but the mass loss of pine branches tended to stagnate in the later stages. Figure 7 As can be seen, after 72 h of treatment in a NMP∶H2O = 4∶6 mixed solvent system, the residual mass of pine branches was 0.364 g, while that of corn stalks was 0.074 g, a difference of approximately 0.29 g. This indicates that the degradation degree of corn stalks in this system was significantly higher than that of pine branches. For corn stalks, as the treatment time increased from 24 h to 72 h, the residual mass continuously decreased from 0.316 g to 0.074 g, showing a clear time-dependent decreasing trend. In contrast, the residual mass of corn stalks after 72 h of treatment in pure water was 0.307 g, while the residual mass in the mixed solvent system at the same time was only 0.074 g, a difference of approximately 0.233 g. The residual mass in the mixed solvent system was less than one-quarter of that in the pure water system. In summary, there are significant differences in the degradation response of the two biomass types to the same mixed solvent system, with corn stalks showing a significantly better degradation effect than pine branches. Furthermore, the mixed solvent system showed a significantly better treatment effect on corn stalks than the single water system.

[0038] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.

Claims

1. The application of a ZnO@Fe3O4 composite catalytic material in the treatment of plant waste, characterized in that, Includes the following steps: Plant waste treatment liquid is added to a dual-electrode reactor. The working electrode of the dual-electrode reactor is a carbon cloth coated with ZnO@Fe3O4 composite catalyst material, and the counter electrode is a carbon rod. At room temperature, the plant waste is degraded by alternating current treatment.

2. The application of the ZnO@Fe3O4 composite catalytic material according to claim 1 in the treatment of plant waste, characterized in that, The frequency of the AC power processing is 1μHz-1000Hz, and the AC power processing time is 60-180min.

3. The application of the ZnO@Fe3O4 composite catalytic material according to claim 2 in the treatment of plant waste, characterized in that, The electrical signal waveform for AC processing is selected from sine wave, triangle wave, square wave, noise wave, pulse wave, or singer function waveform.

4. The application of the ZnO@Fe3O4 composite catalytic material according to claim 3 in the treatment of plant waste, characterized in that, The electrical signal waveform for AC power processing is selected from the Singer function waveform.

5. The application of the ZnO@Fe3O4 composite catalytic material according to claim 4 in the treatment of plant waste, characterized in that, The frequency of the AC power processing is 10 Hz, and the AC power processing time is 180 min.

6. The application of the ZnO@Fe3O4 composite catalytic material according to claim 1 in the treatment of plant waste, characterized in that, The preparation method of the ZnO@Fe3O4 composite catalytic material includes the following steps: adding zinc nitrate hexahydrate and hexamethylenetetramine to water, mixing well to obtain a precursor solution, adding ferric nitrate nonahydrate to the precursor solution, continuing to mix well, carrying out a hydrothermal reaction, cooling to room temperature, centrifuging, washing, and drying to prepare the ZnO@Fe3O4 composite catalytic material.

7. The application of the ZnO@Fe3O4 composite catalytic material according to claim 6 in the treatment of plant waste, characterized in that, The molar ratio of zinc nitrate hexahydrate, hexamethylenetetramine, and ferric nitrate nonahydrate is 12:12:1; the hydrothermal reaction is carried out at a temperature of 95°C for 4 hours.

8. The application of the ZnO@Fe3O4 composite catalytic material according to claim 1 in the treatment of plant waste, characterized in that, The preparation method of the plant waste treatment liquid includes the following steps: drying and pulverizing the plant waste, adding the obtained plant waste powder to a mixed solvent of N-methylpyrrolidone and water to obtain the plant waste treatment liquid.

9. The application of the ZnO@Fe3O4 composite catalytic material according to claim 8 in the treatment of plant waste, characterized in that, The volume ratio of N-methylpyrrolidone to water is 4:6; The ratio of plant waste powder to mixed solvent is 0.62g:35mL.